Pengaruh Kapasitas Sumber Daya Manusia, Pemanfaatan Teknologi Informasi, dan Pengendalian Intern Akuntansi terhadap Nilai Informasi Pelaporan Keuangan Pemerintah Daerah (Studi Kasus pada Dinas Kabupaten Wonogiri) - Sierad Azhari, Riskhi Diah; , Drs. Yuli Tri Cahyono , M.M., Akt., CA (2016)
The quality of information in financial reporting is strongly influenced by the capacity of the human resources that work well in the preparation of government financial reporting. The use of existing information technology have not yet been able to fully utilized, then the implementation of information technology to be futile and increasingly expensive. This study aims to provide empirical evidence of the influence of human resource capacity, utilization of information technology and internal control of financial reporting information terhdap value of local government in the Office of Wonogiri. This research is an empirical study using survey methods. Data were collected by questionnaires. Samples were obtained 48 respondents. Data were analyzed using multiple linear regression analysis. Based on the analysis we can conclude that the human resource capacity, utilization of information technology, accounting and internal control affect the value of the local government financial reporting information in the Office of Wonogiri. This can be shown by each of the variables p value <0.05. So those hypotheses from H1 until H3 have an effect.